Knowledge requirements, tax complexity, compliance costs and tax compliance in Uganda - Doreen Musimenta (Cogent Business & Management, 2020)
The purpose of this study is to examine the relationship between knowledge requirements, complexity of the tax system and tax compliance in Uganda while exploring the indirect effects of compliance costs. The research design was cross sectional and correlational using VAT registered withholding agents. This study results suggest that knowledge requirements do not have a significant relationship with compliance costs. Knowledge requirements are best suited in explaining the internal costs of compliance than external costs. Our results indicated that taxpayers have sufficient tax knowledge to enable them comply with taxes but that does not rule out the fact that taxpayers still incur the cost of complying. When the system of taxation becomes more complex, then the cost of complying also becomes high. The complex tax systems require taxpayers to obtain extra training as well as seeking external professional advice in order to comply. Therefore, that tax complexity has a direct and indirect impact (through compliance costs) on tax compliance. Rather than focusing only on the importance of the normal analytical deliberation of knowledge requirements and tax complexity by taxpayers in influencing their tax compliance, the current paper shows that in addition, the indirect effect of compliance costs in establishing the basis for understanding taxpayers' compliance. Methodologically, this study solicits responses from taxpayers who are deemed to be tax compliant and have been designated to withhold VAT (which is one of the biggest indirect taxes collected in Uganda) in addition to paying income taxes. This probably offers a unique way of deriving better results than previous studies which have basically concentrated on just taxpayers regardless of whether they are presumed compliant or not.
Keywords: 650; knowledge requirements; tax complexity; compliance costs; tax compliance; Uganda; tax agents